Polarization-Independent Two-Layer Grating With Five-Port Splitting Output Under Normal Incidence - Bowen Gong; Huiying Wen; Hongtao Li (IEEE Photonics Journal)
In this paper, we report a two-layer five-port diffraction grating by a polarization-independent design under normal incidence. To be different from conventional five-port gratings, initially, we design a novel two-layer grating with operation in transmission. Next, we firstly design a polarization-independent grating with five-port splitting output. On the one hand, the accurate grating vector parameters are optimized using rigorous coupled-wave analysis (RCWA) approach. On the other hand, the inherent coupling mechanism happened in the grating region can be well explained by employing simplified modal method (SMM). More importantly, all reported conventional five-port beam splitter gratings were designed based on polarization dependent. Although they could obtain high diffraction efficiency for TE or TM polarization, it requires more complicated and time-consuming fabrication processes in practical grating applications. Thus, this work can open up a possible thought for designing polarization-independent multi-port beam splitter diffraction gratings.